2020
DOI: 10.1101/2020.10.02.20202614
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined Metabolic Activators accelerates recovery in mild-to-moderate COVID-19

Abstract: BACKGROUND The characteristics of COVID-19 outbreak and high fatality rate of COVID-19 infection have attracted the attention of scientists due to the strong interactions between components of metabolic syndrome, metabolic abnormalities, and viral pathobiology of COVID-19. Combined metabolic cofactors supplementation (CMCS) consisting of L-serine, N-acetyl-L-cysteine (NAC), nicotinamide riboside (NR), and L-carnitine tartrate is being studied for the treatment of patients with COVID-19. METHODS We conducted a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 47 publications
7
28
0
Order By: Relevance
“…The 91 included trials enrolled a total of 46,802 patients between January 18 (first recruitment) and October 4 (last recruitment). Included trials evaluated one or more drugs (n = 76, [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , ...…”
Section: Resultsmentioning
confidence: 99%
“…The 91 included trials enrolled a total of 46,802 patients between January 18 (first recruitment) and October 4 (last recruitment). Included trials evaluated one or more drugs (n = 76, [13] , [14] , [15] , [16] , [17] , [18] , [19] , [20] , [21] , [22] , [23] , [24] , [25] , [26] , [27] , [28] , [29] , [30] , [31] , [32] , [33] , [34] , [35] , [36] , [37] , [38] , [39] , [40] , [41] , [42] , [43] , [44] , [45] , [46] , [47] , [48] , [49] , [50] , [51] , [52] , [53] , [54] , [55] , [56] , [57] , [58] , [59] , [60] , [61] , [62] , [63] , [64] , [65] , [66] , [67] , [68] , [69] , [70] , [71] , [72] , [73] , [74] , ...…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, declines in tryptophan-derived de novo nicotinamide synthesis is associated with aging and in ammation, 70 suggesting that nutritionally replenishing NAD reservoirs (e.g., nicotinamide riboside) may be therapeutic in facilitating recovery from severe COVID-19. 71 Depleting tryptophan to promote kynurenine synthesis may also lead to serotonin depletion, a key component of platelet dense granules with a role in platelet activation. 72 This is relevant given the importance of coagulopathy in COVID-19, with increased plasma levels of FVIII, D-dimers, and VWF (i.e., increased VWF:collagen binding activity, increased VWF:ADAMTS-13 activity ratio), which are among the top correlates of mortality in our cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Only two patients in the intervention group (2.8%) reported a similar adverse event of mild rash on the upper part of the body. 72 A case report of a 54-year-old male patient with preexisting hypertension, hyperlipidemia, and obesity who was tested positive for COVID-19 11 days prior to admission to Holy Family Hospital in Massachusetts showed that combination therapy of hydroxychloroquine and N-acetylcysteine led to a progressive clinical improvement and a decrease in inflammatory markers for inflammation, for instance, C-reactive protein and lactic acid. The patient was mechanically ventilated for only 3 days, was then transferred from the ICU to the general ward on Day 7, and was finally discharged from the hospital on Day 12 with stable vital signs and normalized laboratory results.…”
Section: Clinical Trialsmentioning
confidence: 99%
“…In non-G6PD deficient patients, significant overall reductions in inflammatory markers (C-reactive protein and ferritin) were observed with the use of N-acetylcysteine. Altay et al (2020), Turkey 72 Single center, double-blind, randomized, open-label, placebo-controlled trial, Phase 2 Adults aged 18 years or older with confirmed COVID-19 within 24 hours and had a stable clinical course 100 Hydroxychloroquine of an initial dose of 2×400 mg orally, followed by 400 mg/day (2x200 mg) for 5 days. Subsequently, a combined metabolic cofactors supplementation (CMCS) comprising L-carnitine tartrate 7.46 g/day, N-acetylcysteine 5.1 g/day, Nicotinamide riboside 2 g/day plus Serine 24.7 g/day was given orally twice a day for 14 days (n=71).…”
Section: Clinical Trialsmentioning
confidence: 99%
See 1 more Smart Citation